Pelatihan Hukum Bisnis Kepada Pimpinan Lembaga Keuangan - Suwinto Johan; Ariawan Gunadi; Indah Siti Aprilia; Gunardi Lie (STMIK Royal, 2022)
Abstract: Business actors need information regarding the implications of the latest laws and regulations for their business activities. Many companies have carried out corporate action activities during the Covid-19 pandemic. This corporate action requires approval from creditors, especially bank financial institutions. Bank leaders need knowledge of regulations and the implications of each regulation on decisions to be taken. This training provides information on new regulations, including the Job Creation Law, Information and Electronic Transaction Law, and the proposed Personal Data Protection (PDP Law. The training is conducted using the webinar method in order to reach bank leaders throughout Indonesia. The results of this webinar have enriched the knowledge of bank leaders regarding the laws and regulations, especially their implications for the banking business. Keywords: corporate action; business law; banking Abstrak: Pelaku usaha memerlukan informasi mengenai implikasi peraturan perundang-undangan terbaru terhadap kegiatan usaha yang dijalankannya. Banyak perusahaan telah melakukan kegiatan aksi korporasi selama pandemi Covid-19. Aksi korporasi ini memerlukan persetujuan dari pada kreditor, khususnya lembaga keuangan bank. Para pimpinan bank memerlukan pengetahuan mengenai peraturan dan implikasi setiap peraturan terhadap keputusan yang akan diambil. Pelatihan ini memberikan informasi mengenai peraturan yang baru, di antaranya UU CK, UU ITE, dan rencana UU PDP. Pelatihan dilakukan dengan metode webinar agar dapat menjangkau para pimpinan bank yang berada di seluruh Indonesia. Hasil webinar ini telah memperkaya pengetahuan para pimpinan bank terhadap peraturan perundang-undangan terutama implikasinya terhadap bisnis perbankan.Kata Kunci: aksi korporasi; hukum bisnis; perbankan.